Teclistamab in relapsed or refractory AL amyloidosis: a multinational retrospective case series - Forgeard, Nathalie; Elessa, Dikélélé; Carpinteiro, Alexander; Belhadj, Karim; Minnema, Monique; Roussel, Murielle; Huart, Antoine; Javaugue, Vincent; Pascal, Laurent; Royer, Bruno; Talbot, Alexis; Gounot, Romain; et al. (Blood, 2024)
TO THE EDITOR:AL amyloidosis is a rare condition characterized by the deposition of misfolded immunoglobulin light chains produced by clonal plasma cells or lymphoplasmacytic cells. Treatment aims at reducing the production of pathogenic free light chains (FLCs) to prevent organ damage. Deep and sustained hematologic response (HemR) correlates with organ function improvement and with survival outcomes.1 Current guidelines recommend a regimen containing daratumumab, bortezomib, cyclophosphamide, and dexamethasone2 for patients with newly diagnosed AL amyloidosis. Although this treatment results in high response rates,3 a proportion of patients are refractory or eventually relapse. The use of immunomodulatory drugs (IMiDs) or carfilzomib can be hampered by kidney injury or cardiovascular issues. Hence, new treatment options for patients with relapsed or refractory (R/R) AL remain an unmet medical need. Teclistamab, a bispecific T-cell engager (BCMA × CD3) antibody, has recently been approved for the treatment of R/R multiple myeloma (MM). Overall response rate in a phase 1 to 2 study of myeloma patients was 63%, with 26.7% reaching minimal residual disease negativity.4 Main safety concerns are the occurrence of cytokine release syndrome (CRS), immune cell-associated neurological symptoms (ICANS), and infections. There were no signals related to cardiac or kidney toxicity. Herein, we report data about safety and efficacy from patients with R/R AL treated with teclistamab in a real-life setting.
Online verfügbar 17 December 2023, Version des Artikels 22 February 2024
Gesehen am 02.10.2024